The complete chloroplast genome sequence of the leafy bladderwort, Utricularia foliosa L. (Lentibulariaceae) - Silva, Saura R. [UNESP]; Pinheiro, Daniel G. [UNESP]; Meer, Elliott J.; Michael, Todd P.; Varani, Alessandro M. [UNESP]; Miranda, Vitor F. O. [UNESP] (Springer Nature, 2017)
Utricularia foliosa L., commonly known as leafy bladderwort, is a widespread aquatic carnivorous plant from the Lentibulariaceae family. The species of the Utricularia and Genlisea genera are known to possess the smallest nuclear genomes across angiosperms. This study reveals that U. foliosa have a typical chloroplast genome of 150,851 bp in length, comprised of a large single-copy region (LSC) of 82,720 bp, a small single-copy region (SSC) of 17,481 bp, and inverted repeat regions (IRs) of 25,325 bp. A total of 139 genes, 88 of which are protein coding genes, 37 tRNA genes, eight rRNA genes and six pseudogenes were identified. All plastid NAD(P)H-dehydrogenase genes are present as intact copies. Phylogenetic analyses indicate that U. foliosa is closely related to other suspended or affixed aquatic species belonging to the Utricularia sect. Utricularia.
Keywords: Bladderwort; Carnivorous plant; CpDNA; Lentibulariaceae; Plastome